Skyscapers and greenery. An unprecedented symbiosis - Simona Talenti; Annarita Teodosio (Agathón)
An appropriate use of natural resources, combined with the choice of innovative materials and the reduction of the consumption of non-renewable sources, increasingly contribute to the sustainability of skyscrapers. Italy has also witnessed the growing custom of including green elements in tall buildings, in the envelopes, at the bases, sides or interiors. The use of vegetation not only concerns new constructions, but also the redevelopment of existing towers, sometimes offering a chance even to buildings that originally lack significant value. Greenery applied to Italian skyscrapers, however, should raise questions about the actual environmental, economic and social sustainability of these design solutions, which sometimes seem to respond to mere aesthetic and ornamental requirements or marketing demands. Through the analysis of certain Italian skyscrapers characterized by the presence of greenery, this study aims to underline the potential and the importance of the use of vegetation in the tall building, an architectural type historically in contrast with natural elements, triggering a reflection on intervention criteria susceptible of application also at wider and more differentiated scales.